Efektifitas Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Kemampuan Berpikir Kritis Matematis dan Kemandirian Belajar Siswa - Sutrisno Sutrisno; Sa’ad Konaah; Intan Indiati (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
This research is motivated by mathematical critical thinking skills and students' learning independence that is not yet optimal becomes something that teachers need to pay attention to their students by providing an appropriate learning model to foster this. Based on the 2013 curriculum advocates the development of learning outcomes in cognitive and affective components developed simultaneously and proportionally. This study aims to determine the effectiveness of Jigsaw type cooperative learning models on mathematical critical thinking skills and student learning independence. This type of research is a quasi-experimental research. This study uses a Pretest-Posttest Control Group Design research design. The research instrument was tested for validation by content validation before being trialled. Data analysis techniques in this study were Multavariate Normality Test, Covariance Matter Homogeneity Test, Hotelling Trace T2 Test and t Test. In the preliminary data analysis, which was taken from the daily test scores and scale sheets of the pretest attitude of students' learning independence, showed there was no difference in the average mathematical critical thinking ability and student learning independence between the experimental class and the control class. In the final data analysis taken from the posttest, it can be concluded that the average mathematical critical thinking ability that uses the Jigsaw type cooperative learning model is better than the conventional learning model. But the results of the study also showed the average independence of student learning using the Jigsaw type cooperative learning model is the same as the conventional learning model.